ANALISIS MELODI LAGU DONNA LEE KARYA CHARLIE PARKER PADA INSTRUMEN ALTO SAXOPHONE - Andani, Yudhis Chitra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe background of this research was Donna Lee Charlie Parker's work has the characteristics of a very fast tempo. The choice of tone on Alto Saxophone played by Parker is very unique, there is also a section of Alto Saxophone solo that Parker plays. Donna Lee's song by Charlie Parker is often associated with the Jazz Bebop genre. Therefore, the melody of Donna Lee's song on Alto Saxophone is very interesting to be analyzed further. In addition, there are many Jazz events in Indonesia has not been matched by comprehensive Jazz studies. On the other hand, the realm of Bebop is still limited to be studied and revealed musical facts.Based on those background, this research problem were